The long arm of papal authority : late medieval Christian peripheries and their communication with the Holy See - Jaritz, Gerhard, 1949-; Jørgensen, Torstein, 1951-; Salonen, Kirsi (CEU medievalia, 2005)
The volume contains selected papers from two conferences in 2003, at the University of Bergen (Norway) and at CEU. They deal comparatively with the communication of the Holy See with Northern Europe and Eastern Central Europe in the Late Middle Ages, both areas at the margins of Western Christendom. Special emphasis is placed on the analysis of the registers of the Apostolic Penitentiary.